2022
DOI: 10.3389/fcvm.2022.1020054
|View full text |Cite
|
Sign up to set email alerts
|

Different mechanisms of mitral regurgitation in hypertrophic cardiomyopathy: A clinical case and literature review

Abstract: BackgroundAbnormalities of the mitral valve (MV) apparatus are typical features of hypertrophic cardiomyopathy (HCM). These abnormalities include leaflet elongation, thick leaflets, displacement of papillary muscle, and systolic anterior motion (SAM) of the MV anterior leaflet. Mitral valve chordal rupture associated with HCM is a rare but serious issue capable of change the clinical apparence and the prognosis of the patient.Case summaryA 57-year-old lady with a history of diabetes, dyslipidemia, and a previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…It has been associated with effective outcomes with minimal complications. Furthermore, MVR surgery has also been implemented for these patients to correct MV malformations caused by this disorder 21 and reduce LVOT gradient, resulting in decent symptom relief and acceptable complications. 22 , 23 The treatment team should carefully select the type of surgical treatment for each HCM patient, considering the patient's unique characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…It has been associated with effective outcomes with minimal complications. Furthermore, MVR surgery has also been implemented for these patients to correct MV malformations caused by this disorder 21 and reduce LVOT gradient, resulting in decent symptom relief and acceptable complications. 22 , 23 The treatment team should carefully select the type of surgical treatment for each HCM patient, considering the patient's unique characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with obstructive HCM, the mitral leaflet can be retracted by the abnormally fibrotic secondary chordae, and chordal resection can let the tethered leaflet fall posteriorly and away from the septum [ 6 , 46 ] (Fig. 3 ).…”
Section: Procedures On the Mitral Chordaementioning
confidence: 99%
“…Studies examining the mitral valve in patients with HCM have shown that the mitral valve itself can be structurally altered [8,9]. Therefore, a detailed evaluation of the anatomy and function of the mitral valve, as well as the significance of mitral regurgitation (MR), is essential in patients with HCM [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining the mitral valve in patients with HCM have shown that the mitral valve itself can be structurally altered [8,9]. Therefore, a detailed evaluation of the anatomy and function of the mitral valve, as well as the significance of mitral regurgitation (MR), is essential in patients with HCM [8][9][10][11]. The aim of our study is to examine the potential influence of moderate or moderately severe MR on the prognosis, clinical presentation, and structural characteristics of HCM patients.…”
Section: Introductionmentioning
confidence: 99%